Penerapan Strategi Diversifikasi dalam Pembentukan Portofolio Optimal Menggunakan Model Markowitz - Suriani M; Dian Firmayasari S; Harianto Harianto; Nur Sipa; Serli Alifia; Dirman Dirman (Universitas Cokroaminoto Palopo, 2026)
Investments made by investors are generally influenced by the level of return and risk. Therefore, to address this risk, investors can conduct an analysis in advance by diversifying their portfolios. The purpose of this study is to form an optimal portfolio using the Markowitz model so that it can be used as a basis for investment considerations. The data used in this study is secondary data, namely monthly stock data from four companies listed on the Indonesia Stock Exchange (IDX) for the period January 2025 - January 2026 and whose shares are listed on the Liquid 45 (LQ45) index, obtained from the official Yahoo Finance website. The results of the study show that there are three portfolios that fall into the category of optimal portfolios based on the Markowitz efficient portfolio concept, namely portfolio 1 (a combination of PT Bank Syariah Indonesia Tbk and PT Bank Negara Indonesia (Persero) Tbk stocks), with the highest expected return of 10.47% and a risk of 8.12%. Portfolio 3 (a combination of PT Bank Syariah Indonesia Tbk and PT Bank Central Asia Tbk stocks), which offers a balance between return and risk with the same value of 7.45%. Portfolio 5 (a combination of PT Bank Tabungan Negara (Persero) Tbk and PT Bank Central Asia Tbk shares), with the lowest risk level of 5.92% and an expected return of 5.69%.